The Influence of Lifestyle, Reference Group, and Electronic Word of Mouth on The Decision to Purchase Haircut Services Jack Barbershop City Kediri - Oktavian, Iqbal; Akbar, Taufik; Prasasti, Karari Budi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of life style, reference group, and E-WOM on purchasing decisions. This study uses a quantitative approach with the multiple linear analysis method. The data were collected through questionnaires with a Likert scale and analyzed using SPSS software version 26. The results of this study indicate that both partially and simultaneously the variables of life style, reference group, and electronic word of mouth (E-WOM) have a significant effect on purchasing decisions. The coefficient of determination supports the results of this study by showing that 80.1% of the independent variable affects the dependent variable and the rest is influenced by other factors. The role of independent variables in this study as information and recommendations in shaping purchasing decisions consumers in using haircut services at Jack Babershop Kota Kediri.